Head trauma is the major risk factor for cerebral sinus-vein thrombosis. (January 2016) - Giladi, Ornit; Steinberg, David M.; Peleg, Kobi; Tanne, David; Givon, Adi; Grossman, Ehud; Klein, Yoram; Avigdori, Shirli; Greenberg, Gahl; Katz, Rachel; Shalev, Varda; Salomon, Ophira
Abstract: Background: Cerebral sinus vein thrombosis (CSVT) is a rare disease with significant neurological sequelae and high mortality rate. Incidence of CSVT diagnosis in the western world has increased despite the reduced occurrence of infections. Aim: To identify risk factors that may explain the predisposition to site specific thrombosis. Methods: Ninety consecutive patients diagnosed with acute CSVT in tertiary hospital. As a control group we used the data extracted from the National Trauma Registry and Healthcare Services. Results: Trauma history up to one month prior to diagnosis of CVST was found in 13 (14%) patients. Six patients had skull fractures, the others had blunt trauma. The overall SMR was 941 (p < 0.0001); the separate results for men and women were 1206 and 543, respectively. Infections confined to the head and neck in 7% of the cases and brain tumor were observed in 8%. At the time of CVST, 23 of 50 (46%) women had a hormonal risk factor. The SMR for OC use was 1.63 (p = 0.0298). Prothrombotic polymorphisms were detected in 16 of 63 (25.4%) patients who were tested for factor V Leiden and prothrombin G20210A mutation (OR = 3.47, p = 0.002) in comparison to 49% in DVT patients (OR = 9.95, p < 0.0001). Conclusions: Assessment for CVST in patients with recent trauma and headache even after intact head CT is required. The other risk factors, such as hormone related and prothrombotic polymorphisms, were not specific just for CVST and the latter play a lesser role in CVST than in DVT. Highlights: Our data support the concept that assessment for CVST is most strongly indicated following head and neck trauma Hormone related and prothrombotic polymophisms, were not specified just for CVST and the latter play a lesser role in CVST than in DVT Strong relationships were not found between potential risk factors and disease outcomes.